Alcohol Expectancies dan Perilaku Mengonsumsi Alkohol pada Remaja di Surabaya - Anissa Cessarea; Ananta Yudiarso; Yusti Probowati Rahayu (Perpustakaan Universitas Surabaya, 2020)
Abstract — This study aims to find the role of alcohol expectancies among adolesecents on their drinking behavior. This study was conducted to 360 adolescents in Surabaya who consumed alcohol at least once in the past year, with age range were 15-24 years old. Data on this study is being collected using online questionnaire. Comprehensive Alcohol Expectancy Questionnaire (CAEQ) was used to asses alcohol expectancies. Drinking behavior was assessed by Alcohol Use Disoder Identification Test (AUDIT-C). Data analysis was done using non-parametric analysis : Spearman Rank Order Correlation. The results shows that there are significant correlation between alcohol expectancies and drinking behavior (r=0.250; p=0.000). Furthermore, this study finds significant association between alcohol expectancy aspects and drinking behavior. (1) Social assertiveness and positive affect (r=0.281; p=0.000), (2) Tension reduction (r=0.241; p=0.000) and (3) Sexual Enhancement (r=0.238; p=0.000). This findings explain that social influence, belief that alcohol can be used as a coping to individual stressor and can increase sexual arousal are influencing individual drinking behavior.Keywords: Adolescents, Alcohol Consumption, Alcohol Expectancies Abstrak— Penelitian ini dilakukan untuk mengetahui hubungan antara alcohol expectancy dengan perilaku mengonsumsi alkohol pada remaja. Penelitian dilakukan pada 360 remaja dengan rentang usia 15-24 tahun, pernah mengonsumsi alkohol setidaknya 1x dalam satu tahun terakhir, dan berdomisili di Surabaya. Data dalam penelitian ini dikumpulkan melalui kuisioner online. Variabel Alcohol Expectancy diukur menggunakan skala CAEQ (Comprehensive Alcohol Expectancy Questionnaire) dan perilaku mengonsumsi alkohol diukur menggunakan skala AUDIT-C (Alcohol Use Disorder Identification Test). Hipotesis penelitian dianalisis menggunakan analisis statistik nonparametrik yaitu Spearman Rank Order Correlation. Hasil uji hipotesis menunjukkan bahwa terdapat hubungan antara alcohol expectancy dengan perilaku mengonsumsi alkohol (r=0.250;p=0.000). Selain itu, penelitian ini juga menemukan adanya korelasi antara aspek dalam alcohol expectancy dengan perilaku mengonsumsi alkohol, yaitu aspek 1) Social Assertiveness and Positive Affect (r=0.281;p=0.00), 2) Tension Reduction (r=0.241;p=0.00) dan 3) Sexual Enhancement (r=0.238;p=0.00). Asosiasi ini menunjukkan bahwa lingkungan sosial, harapan bahwa alkohol dapat menjadi coping terhadap stressor dan alkohol dapat meningkatkan gairah seksual, cenderung memengaruhi perilaku mengonsumsi alkohol.Kata kunci: Ekspetansi alkohol, Konsumsi Alkohol, Remaja